Krisis Manusia Moden: Tinjauan Falsafah Terhadap Saintisme dan Relativisme Kultural - W. M, Abdul Hadi (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
The main aim of this paper is to trace the origin of scientism in the history of Western philosophical thought and to discuss its subsequent development and impact of modern Western thought. Scientism, in the author’s view, refers to the system of philosophical thought which has its foundation in the scientific discoveries of Copernicus, Kepler, Galileo, and Newton in the sixteenth and seventeenth centuries. With two other streams of philosophical thought, namely, cultural relativism and nihilism, scientism has exerted a great influence on the thoughts of modern man. In fact, the former two streams have their roots in the historical development of scientism. The main significance of scientism lies in the fact that, in one way or another, it has been inextricably linked to the numerous philosophical system, ideologies, that permeate modern political, economic, and cultural life, as well as the worldviews of contemporary society. This impact of scientism is largely negative. The author tries to show that, together with its various offshoots and other philosophical currents, scientism has been responsible for the marginalization of spirituality and the prevalence of reductionism, which equates knowledge solely with physical power. Scientism has also reduced truth, reality, and the worth of man to their lowest physical levels. The crisis of modern man may be attributed largely to this negative impact of scientism.